2022
DOI: 10.1021/acs.est.1c07923
|View full text |Cite
|
Sign up to set email alerts
|

Global Meta-analysis of Airborne Bacterial Communities and Associations with Anthropogenic Activities

Abstract: Airborne microbiome alterations, an emerging global health concern, have been linked to anthropogenic activities in numerous studies. However, these studies have not reached a consensus. To reveal general trends, we conducted a meta-analysis using 3226 air samples from 42 studies, including 29 samples of our own. We found that samples in anthropogenic activity-related categories showed increased microbial diversity, increased relative abundance of pathogens, increased co-occurrence network complexity, and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 91 publications
(141 reference statements)
1
8
0
2
Order By: Relevance
“…Several studies have compared results obtained by different sampling methods for a given aerosol sample (filter/liquid-based sampler), and bacterial and fungal diversity, and amplicon sequence variants varied greatly between the methodologies 46 , 54 , 56 , 68 . Jiang et al 69 conducted a meta-analysis of 16S rRNA gene amplicon sequencing on 3226 airborne samples, and the results indicated that the significant effect of PCR primer bias on the air bacterial community was higher than environmental variations such as sampling seasons. Furthermore, it has been recognized that NGS is sensitive to environmental DNA contamination during the sample preparation, in particular when treating samples with low microbial biomass 70 .…”
Section: Ngs Methods For Low-biomass Bioaerosolsmentioning
confidence: 99%
“…Several studies have compared results obtained by different sampling methods for a given aerosol sample (filter/liquid-based sampler), and bacterial and fungal diversity, and amplicon sequence variants varied greatly between the methodologies 46 , 54 , 56 , 68 . Jiang et al 69 conducted a meta-analysis of 16S rRNA gene amplicon sequencing on 3226 airborne samples, and the results indicated that the significant effect of PCR primer bias on the air bacterial community was higher than environmental variations such as sampling seasons. Furthermore, it has been recognized that NGS is sensitive to environmental DNA contamination during the sample preparation, in particular when treating samples with low microbial biomass 70 .…”
Section: Ngs Methods For Low-biomass Bioaerosolsmentioning
confidence: 99%
“…Very small quantities of pathogenic bacteria can be transferred with dust particles over very long distances [ 70 ]. The human body surface is a more plausible (compared to other biotopes) source of pathogenic bacteria in the air [ 71 ]. It was revealed that there is a clear dependence between the structure and composition of the bacterial microbiome at an altitude of 10 m above ground level (an island and a peninsula in East Asia) and dust storms in Central Asia [ 69 ].…”
Section: Metagenomic Sequencingmentioning
confidence: 99%
“…A meta-analysis of the results of 42 studies, covering more than 3,000 bioaerosol samples, revealed increased bacterial diversity, and relative abundance of pathogens in the samples associated with anthropogenic activity at collection sites [ 71 ].…”
Section: Metagenomic Sequencingmentioning
confidence: 99%
See 2 more Smart Citations